Differentiating Degradation Characteristics in Lithium-Ion Cells. Issue 11 (18th November 2021) - Saunders, Luke; Wang, Jiabin; Stimming, Ulrich
Abstract : Lithium-ion batteries are prevalent in everyday usage and ensuring they are used efficiently is of paramount concern. The degradation of lithium-ion batteries under cycling can affect various components in the cells. Understanding the degradation characteristics of the cell can aid in ensuring longer lifetime through optimized usage. Long-term automated EIS data collection has been used as a non-destructive tool to track the impedance changes within the cells over time due to repeated cycling. Separating the different degradation factors contributed by the graphite and NMC electrodes in a non-invasive way is still a challenge. In this work, EIS measurements of half-cells dissembled from full cells are shown to provide further insight into cell degradation characteristics. By using this methodology to differentiate the degradation at different electrodes, new materials can be easily screened for their viability in next generation batteries. The methodology also helps estimate the degradation changes with cycling and provides useful information for further understanding the degradation mechanism.